2002
DOI: 10.1002/glia.10100
|View full text |Cite
|
Sign up to set email alerts
|

A new neuromodulatory pathway with a glial contribution mediated via A2a adenosine receptors

Abstract: A low concentration (10 nM) of adenosine potentiated hippocampal neuronal activity via A(2a) adenosine receptors without affecting presynaptic glutamate release or postsynaptic glutamatergic conductance. Adenosine inhibited glutamate uptake through the glial glutamate transporter, GLT-1, via A(2a) adenosine receptors. In addition, adenosine stimulated GLT-1-independent glutamate release from astrocytes, possibly in response to a rise in intracellular Ca(2+), via A(2a) adenosine receptors involving PKA activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(81 citation statements)
references
References 65 publications
4
77
0
Order By: Relevance
“…As expected, adenosine causes a 2 -3-fold increase in glutamate release from cultured hippocampal astrocytes from normal rats and mice (7). A similar increase is obtained with cultured astrocytes from GLT-1 knock-out mice and the glutamate release is not inhibited by the GLT-1 inhibitor dehydrokainic acid or by deleting Na + from extracellular solution (7). These demonstrate that the glutamate release is not due to reverse transport by transporters including GLT-1.…”
Section: Glutamate Release From Astrocytes Via a 2a Adenosine Receptorssupporting
confidence: 79%
See 2 more Smart Citations
“…As expected, adenosine causes a 2 -3-fold increase in glutamate release from cultured hippocampal astrocytes from normal rats and mice (7). A similar increase is obtained with cultured astrocytes from GLT-1 knock-out mice and the glutamate release is not inhibited by the GLT-1 inhibitor dehydrokainic acid or by deleting Na + from extracellular solution (7). These demonstrate that the glutamate release is not due to reverse transport by transporters including GLT-1.…”
Section: Glutamate Release From Astrocytes Via a 2a Adenosine Receptorssupporting
confidence: 79%
“…Astrocytes, alternatively, release neurotransmitters in response to an increase in intracellular Ca 2+ concentrations, which in turn stimulates neurons (2 -6). A low concentration (10 nM) of adenosine facilitates hippocampal neurotransmission, where adenosine does not affect synaptically released glutamate and GABA or postsynaptic glutamatergic and GABAergic conductances (7). Adenosine, on the other hand, inhibits functions of the astrocytic glutamate transporter GLT-1 and stimulated glutamate release via A 2 adenosine receptors involving protein kinase A (PKA) activation (7).…”
Section: Astrocytementioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP directly targets astroglial and neuronal P2X receptors [60] stimulating ATP and glutamate release from astrocytes and modulating the function of postsynaptic receptors [61][62][63][64]. In addition, extracellular adenosine has been shown to induce release of glutamate and NO [65,66] from glial cells. NO, in its turn, enhances vesicular release by stimulating cGMP synthesis at the presynaptic site and upregulates trafficking of AMPA receptors at the postsynaptic site [67].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these predominant synaptic effects, it has also been reported that A 2A R can impact on neuronal metabolism [92] but the functional relevance of this finding remains to be explored. Finally, A 2A R are also located in astrocytes and microglia cells [68,93], where they control the uptake of glutamate [94] and the expression of cytokines [68,93].…”
Section: B Adenosine a 2a Receptor Neuromodulation Systemmentioning
confidence: 99%